Agreeing to be changed: Iterative theatremaking as decentralized pedagogy in English - Kneifel, EJ; Rizzotti, Patrick; Mosher, Jack (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
Formatted as a conversation to reflect its collaborative nature, this article explores an iterative, symbiotic, and decentralized pedagogical paradigm developed at the University of British Columbia, preliminary data for which stemmed from a student-led, devised theatre project staged in July 2022. This article seeks to extrude and articulate the project’s continuous incorporation of its own components — from student anecdotal experience, to the co-construction of language and design, to the accumulation of sheer time — so that similar processes might be reimagined in other pedagogical contexts.